Method for improving activity of zinc oxide piezoelectric photocatalyst
Single crystal ZnO nanoparticle powder is prepared by hydrothermal reaction and heat treatment, and reacts with components such as butyl titanate under ultrasound, heat treatment and annealing, and obtains phase-transform-enhanced ZnO/TiO2 piezoelectric catalyst powder, which solves the problem of low activity of zinc oxide piezoelectric photocatalysts in the prior art, achieves efficient and simple catalyst preparation, and significantly improves catalytic activity.
Patent Information
- Application Number
- CN202411867905.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The existing methods have limited enhancement effects on zinc oxide piezoelectric photocatalysts, complex processes and will reduce performance consistency and stability.
Single-crystal ZnO nanoparticle powder was obtained by hydrothermal reaction and heat treatment, and then reacted with solutions such as butyl titanate and ethanol under ultrasound, heat treatment and annealing, and phase-transform-enhanced ZnO/TiO2 piezoelectric catalyst powder was obtained.
The activity of zinc oxide piezoelectric photocatalysts has been improved by about 4 times, and the process is simple, the materials are common, the cost is low, and the performance consistency and stability are also improved.
Smart Images

Figure CN119657111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of improving catalyst activity and relates to a method for improving the activity of zinc oxide piezoelectric photocatalyst. Background Art
[0002] Catalysts play a very important role in the fields of chemical production, environmental treatment, metal recycling, etc. Due to the unique crystal structure and energy band structure of piezoelectric catalysts, they can generate dynamic piezoelectric electric fields under the action of dynamic external forces, regulate the migration of carriers in the crystal, and finally produce active free radicals with strong redox properties to participate in the catalytic reaction. Piezoelectric catalysts have the advantages of being able to utilize tiny energy in the environment and not being restricted by time and space. They can also be coupled with photocatalysis to further enhance their catalytic activity, thus showing broad application prospects. Zinc oxide (ZnO) has great application potential in the field of catalysis due to its combination of piezoelectric and photocatalytic properties, high chemical stability, low cost, and simple preparation. However, the piezoelectric photocatalytic activity of ZnO is still relatively low, which limits its large-scale practical application.
[0003] In order to promote the practical application of ZnO piezoelectric photocatalysts, researchers have improved the piezoelectric photocatalytic activity of ZnO through modification methods such as morphology design and doping. However, the enhancement effect of these methods on ZnO is still limited. The compounding or doping of more materials will inevitably further increase the preparation cost of ZnO piezoelectric photocatalysts, make its process more complicated, and reduce its performance consistency and stability. Therefore, people urgently need to find new and simple modification methods to improve the piezoelectric photocatalytic activity of ZnO. Summary of the invention
[0004] The purpose of the present invention is to provide a method for improving the activity of zinc oxide piezoelectric photocatalyst, which solves the problems that the existing method has limited enhancement effect on ZnO, complex process and reduces the consistency and stability of ZnO performance.
[0005] The technical solution adopted by the present invention is a method for improving the activity of zinc oxide piezoelectric photocatalyst, and the specific steps are as follows: Step 1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, performing a hydrothermal reaction, centrifuging the precipitate, and then performing a heat treatment to obtain a single crystal ZnO nanoparticle powder; Step 2: Add single crystal ZnO nanoparticle powder and butyl titanate to ethanol under ultrasound, add the mixture to a water-ethanol mixed solution for reaction, centrifuge, wash, dry, and then heat treat after the reaction, cool to room temperature and anneal under different processes to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, thereby improving the activity of zinc oxide piezoelectric photocatalyst.
[0006] The present invention is also characterized in that: In step 1, zinc oxide is replaced by inorganic piezoelectric catalysts and their modified, surface-modified or composite piezoelectric catalysts, etc., specifically including layered transition metal dichalcogenides, bismuth layered structure materials, wurtzite-based semiconductors, graphene, PVDF, g-CN or metal organic framework materials.
[0007] In step 2, TiO2 is replaced by other crystalline phase change materials, including other semiconductor oxides, metals and alloys, specifically titanium dioxide, zirconium oxide, vanadium dioxide, iron-based, titanium-based or aluminum-based.
[0008] The specific method of step 1 is: Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, transferring the hydrothermal solution to a reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100-110°C, the time is 6-8h, after the reaction is completed, the obtained precipitate is centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 50-60°C for 12-16h to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment, the heat treatment temperature is 800 ° C, the time is 2~4h, and the single crystal ZnO nanoparticle powder is obtained after cooling in the furnace. The morphology of the single crystal ZnO nanoparticles is rod-shaped, flake-shaped or spherical. The crystal form of the single crystal ZnO nanoparticle powder is a lead-zinc ore structure with piezoelectric properties, and the size of the nanoparticle powder is 100nm~10μm.
[0009] The specific method of step 2 is: Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:60-70; Step 2.2, add single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mix them under ultrasound, then add them to the water-ethanol mixed solution obtained in step 2.1, stir them thoroughly for 1-1.5 hours, and after the reaction is completed, centrifuge, wash, and dry to obtain a ZnO / TiO2 precursor; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, and cooling to room temperature, and then annealing to obtain a phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the morphology of TiO2 in the ZnO / TiO2 piezoelectric catalyst powder is nanoparticles, the crystal form is anatase phase, and it is uniformly coated on the ZnO surface, wherein the size of the TiO2 nanoparticles is 10~100nm.
[0010] In step 2.2, the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15-20, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15-20.
[0011] In step 2.3, the heat treatment process temperature is 600~800℃, the phase transition temperature of TiO2, the heating rate is 1~5℃ / min, and the holding time is 0.5~3h.
[0012] The cooling method in step 2.3 includes furnace cooling, air cooling or quenching cooling in water; The annealing temperature is 300~500℃ and the annealing time is 1~5h.
[0013] The beneficial effects of the present invention are: (1) The method of improving the activity of zinc oxide piezoelectric photocatalysts of the present invention can be widely applied to the preparation of high-performance piezoelectric photocatalysts, wherein ZnO can be replaced by other semiconductor piezoelectric catalysts, and TiO2 can be replaced by other crystalline phase change materials. The second phase materials and piezoelectric materials used are common and easy to prepare materials, and the composite and heat treatment methods used are mature methods, so that the method provided by the present invention has the advantages of simplicity and high efficiency; (2) The method of improving the activity of zinc oxide piezoelectric photocatalysts of the present invention provides a method for improving the activity of piezoelectric catalysts based on phase change, that is, rather than reducing the interfacial stress between the two-phase materials, the interaction force between the heterogeneous materials is increased by changing the second phase crystal form; (3) The method of the present invention for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: because the lattice distortion of ZnO caused by the phase transition of TiO2 increases the piezoelectric field strength of ZnO, and under the action of the heterojunction of TiO2 and ZnO, the piezoelectric photocatalyst efficiency of ZnO is increased by about 4 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM picture of ZnO / TiO2 obtained in Example 1 of the method for improving the activity of zinc oxide piezoelectric photocatalyst of the present invention; Figure 2 It is the XRD spectrum of the samples obtained in comparative example 1 and example 1 of the method for improving the activity of zinc oxide piezoelectric photocatalyst of the present invention. DETAILED DESCRIPTION
[0015] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0016] The method for improving the activity of zinc oxide piezoelectric photocatalyst of the present invention comprises the following specific steps: Step 1: dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, performing a hydrothermal reaction, centrifuging the precipitate, and then performing a heat treatment to obtain a single crystal ZnO nanoparticle powder. The specific method is as follows: Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, transferring the hydrothermal solution to a reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100-110°C, the time is 6-8h, after the reaction is completed, the obtained precipitate is centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 50-60°C for 12-16h to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment, the heat treatment temperature is 800 ° C, the time is 2~4h, and the single crystal ZnO nanoparticle powder is obtained after cooling in the furnace. The morphology of the single crystal ZnO nanoparticles is rod-shaped, flake-shaped or spherical. The crystal form of the single crystal ZnO nanoparticle powder is a lead-zinc ore structure with piezoelectric properties, and the size of the nanoparticle powder is 100nm~10μm.
[0017] Step 2: adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol under ultrasound, adding them to a water-ethanol mixed solution for reaction, centrifuging, washing, drying, and then heat treating, cooling to room temperature and annealing under different processes to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, the specific method is: Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:60-70; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15-20, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15-20, stirring for 1-1.5 hours, after the reaction is completed, centrifuging, washing, and drying to obtain a ZnO / TiO2 precursor; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, wherein the heat treatment process temperature is the phase change temperature of TiO2 600~800℃, the heating rate is 1~5℃ / min, the holding time is 0.5~3h, and it is cooled to room temperature by furnace cooling, air cooling or quenching cooling in water, and then annealing is performed, the annealing temperature is 300~500℃, and the annealing time is 1~5h to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, the morphology of TiO2 in the ZnO / TiO2 piezoelectric catalyst powder is nanoparticles, the crystal form is anatase phase, and it is uniformly coated on the ZnO surface, wherein the size of the TiO2 nanoparticles is 10~100nm.
[0018] Step 3: Test and evaluate the activity of ZnO / TiO2 powder. The specific steps are as follows: Step 3.1, weigh 100 mg of ZnO / TiO2 catalyst powder and add it to 100 mL of aqueous solution or 100 mL of aqueous solution containing dye, precious metal particles or lithium ion positive electrode material, and obtain a suspension after ultrasonic dispersion for 5 min. The suspension is placed in a dark environment and continuously magnetically stirred for 30 min to achieve adsorption-desorption equilibrium; Step 3.2: Transfer the solution obtained in step 3.1 to an ultrasonic generator, turn on ultrasonic / ultraviolet light, test the catalytic efficiency of the sample, and evaluate its piezoelectric photocatalytic activity. Use a UV-visible spectrophotometer to measure the degradation efficiency of the dye, and calculate its photocatalytic efficiency and kinetic constants. The ultrasonic frequency used is 30 ~ 60kHz, the ultrasonic power is 100W, the ultraviolet lamp power is 3W, and the ultrasonic circulating water temperature is 25~45℃.
[0019] The zinc oxide piezoelectric photocatalyst prepared according to the preparation method of the zinc oxide piezoelectric photocatalyst can be used for ultrasonic catalytic degradation of organic pollutants, ultrasonic catalytic production of hydrogen peroxide, and ultrasonic catalytic acceleration of the leaching of precious metals and valuable metals in waste lithium-ion battery positive electrode materials.
[0020] In the preparation method of the zinc oxide piezoelectric photocatalyst of the present invention, the zinc oxide in step 1 is replaced by an inorganic piezoelectric catalyst and their modified, surface-modified or composite piezoelectric catalysts, etc., specifically including layered transition metal dichalcogenides, bismuth layered structure materials, wurtzite-based semiconductors, graphene, PVDF, g-CN or metal organic framework materials.
[0021] In the preparation method of the zinc oxide piezoelectric photocatalyst of the present invention, TiO2 in step 2 is replaced by other crystalline phase change materials, including other semiconductor oxides, metals and alloys, specifically titanium dioxide, zirconium oxide, vanadium dioxide, iron-based, titanium-based or aluminum-based.
[0022] Example 1 The method for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: Step 1: Preparation of ZnO nanorod powder Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, the hydrothermal solution was transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 100°C for 8 hours. After the reaction was completed, the obtained precipitate was centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 60°C for 12 hours to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment at a temperature of 800°C for 4 hours, and obtaining single crystal ZnO nanoparticle powder after cooling in the furnace, the size of which is about 10 μm.
[0023] Step 2: Preparation of TiO2 / ZnO piezoelectric catalyst Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:60; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15, and the mixture is stirred for 1.5 hours. After the reaction is completed, the ZnO / TiO2 precursor is obtained by centrifugation, washing, and drying; Step 2.3, the ZnO / TiO2 precursor is placed in a muffle furnace for heat treatment, wherein the heat treatment process temperature is 800°C, the phase change temperature of TiO2, the heating rate is 1°C / min, the holding time is 2h, and it is cooled to room temperature by furnace cooling, and then annealed at 300°C for 5h to obtain a phase change enhanced ZnO / TiO2 piezoelectric catalyst powder. The SEM photo of the ZnO / TiO2 nanorod powder is shown in Figure 1 As shown, the size of the TiO2 nanoparticles is 200nm.
[0024] Step 3: Evaluation of the activity of TiO2 / ZnO piezoelectric catalyst Step 3.1: Weigh 100 mg of catalyst powder and add it to 100 mL of 10 mg / L Rhodamine B solution. After ultrasonic dispersion for 5 min, the suspension was placed in a dark environment and continuously stirred magnetically for 30 min to achieve adsorption-desorption equilibrium.
[0025] Step 3.2: Transfer the solution obtained in step 3.2 to an ultrasonic generator, turn on the ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 30kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 25°C. Test the piezoelectric photocatalytic efficiency of the sample. Use a UV-visible spectrophotometer to measure the degradation efficiency of the dye and calculate its photocatalytic efficiency.
[0026] Example 2 The method for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: Step 1: Preparation of ZnO nanorod powder Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, the hydrothermal solution was transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 110°C for 6 hours. After the reaction was completed, the obtained precipitate was centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 50°C for 16 hours to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment at a temperature of 800°C for 2 hours, and obtaining single crystal ZnO nanosheet powder after cooling in the furnace, the size of which is about 0.5 μm.
[0027] Step 2: Preparation of TiO2 / ZnO piezoelectric catalyst Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:70; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:20, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:20, stirring for 1 hour, after the reaction is completed, centrifuging, washing, and drying to obtain a ZnO / TiO2 precursor; Step 2.3, place the ZnO / TiO2 precursor in a muffle furnace for heat treatment, wherein the heat treatment process temperature is 600°C, the phase change temperature of TiO2, the heating rate is 2°C / min, the holding time is 0.5h, and it is cooled to room temperature by air cooling, and the cooling rate is controlled to be 10°C / min. Then, annealing treatment is performed, the annealing temperature is 500°C, and the annealing time is 1h to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the size of the TiO2 nanoparticles is 10nm.
[0028] Step 3. Evaluation of the activity of TiO2 / ZnO piezoelectric catalyst Step 3.1: Weigh 100 mg of catalyst powder and add it to 100 mL of 10 mg / L Rhodamine B solution. After ultrasonic dispersion for 5 min, place the suspension in a dark environment and continue magnetic stirring for 30 min to achieve adsorption-desorption equilibrium.
[0029] Step 3.2, transfer the solution obtained in step 3.2 to an ultrasonic generator, turn on ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 40kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 35°C. Test the piezoelectric photocatalytic efficiency of the sample. Use a UV-visible spectrophotometer to measure the degradation efficiency of the dye and calculate its photocatalytic efficiency.
[0030] Example 3 The method for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: Step 1: Preparation of ZnO nanorod powder Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, the hydrothermal solution was transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 105°C for 7 hours. After the reaction was completed, the obtained precipitate was centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 55°C for 14 hours to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment at a temperature of 800°C for 4 hours, and obtaining single-crystalline ZnO nanoparticle powder after cooling in the furnace, the size of which is about 0.1 μm.
[0031] Step 2: Preparation of TiO2 / ZnO piezoelectric catalyst Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:65; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:18, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:18, stirring for 1 hour, after the reaction is completed, centrifuging, washing, and drying to obtain a ZnO / TiO2 precursor; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, wherein the heat treatment process temperature is 700°C, the phase change temperature of TiO2, the heating rate is 5°C / min, the holding time is 1.5h, and cooled to room temperature by furnace cooling, air cooling or quenching cooling in water, and then annealing is performed at 400°C and annealing time is 1h to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the size of the TiO2 nanoparticles is 50nm.
[0032] Step 3: Evaluation of the activity of TiO2 / ZnO piezoelectric catalyst Step 3.1: Weigh 100 mg of catalyst powder and add it to 100 mL of 10 mg / L Rhodamine B solution. After ultrasonic dispersion for 5 min, the suspension was placed in a dark environment and continuously magnetically stirred for 30 min to achieve adsorption-desorption equilibrium.
[0033] Step 3.2, transfer the solution obtained in step 3.2 to an ultrasonic generator, turn on ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 50kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 45°C. Test the piezoelectric photocatalytic efficiency of the sample. Use a UV-visible spectrophotometer to measure the degradation efficiency of the dye and calculate its photocatalytic efficiency.
[0034] Example 4 The method for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: Step 1: Preparation of ZnO nanorod powder Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, the hydrothermal solution was transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 100°C for 7 hours. After the reaction was completed, the obtained precipitate was centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 50°C for 12 hours to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment at a temperature of 800°C for 3.5 hours, and obtaining single-crystalline ZnO nanoparticle powder after cooling in the furnace, the size of which is about 5 μm.
[0035] Step 2: Preparation of TiO2 / ZnO piezoelectric catalyst Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:70; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15, and the mixture is stirred for 1.5 hours. After the reaction is completed, the ZnO / TiO2 precursor is obtained by centrifugation, washing, and drying; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, wherein the heat treatment process temperature is 750°C, the phase change temperature of TiO2, the heating rate is 5°C / min, the holding time is 2h, and it is cooled to room temperature by furnace cooling, air cooling or quenching in water, and then annealing is performed at 350°C and annealing time is 2h to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the size of the TiO2 nanoparticles is 100nm.
[0036] Step 3: Evaluation of the activity of TiO2 / ZnO piezoelectric catalyst Step 3.1: Weigh 100 mg of catalyst powder and add it to 100 mL of 10 mg / L Rhodamine B solution. After ultrasonic dispersion for 5 min, the suspension was placed in a dark environment and continuously stirred magnetically for 30 min to achieve adsorption-desorption equilibrium.
[0037] Step 3.2: Transfer the solution obtained in step 3.2 to an ultrasonic generator, turn on the ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 60kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 25°C. Test the piezoelectric photocatalytic efficiency of the sample. Use a UV-visible spectrophotometer to measure the degradation efficiency of the dye and calculate its photocatalytic efficiency.
[0038] Example 5 The method for improving the activity of zinc oxide piezoelectric photocatalyst is as follows: Step 1: Preparation of ZnO nanorod powder Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1, and the mass ratio of zinc nitrate hexahydrate to deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, the hydrothermal solution was transferred to a 100 mL reactor for hydrothermal reaction at a temperature of 105°C for 6 hours. After the reaction was completed, the obtained precipitate was centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 55°C for 14 hours to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment at a temperature of 800°C for 4 hours, and obtaining single crystal ZnO nanoparticle powder after cooling in the furnace, the size of which is about 10 μm.
[0039] Step 2: Preparation of TiO2 / ZnO piezoelectric catalyst Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:60; Step 2.2, adding single crystal ZnO nanoparticle powder and butyl titanate to ethanol and mixing them under ultrasound, and then adding them to the water-ethanol mixed solution obtained in step 2.1, wherein the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15, stirring for 1 hour, after the reaction is completed, centrifuging, washing, and drying to obtain a ZnO / TiO2 precursor; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, wherein the heat treatment process temperature is 800°C, the phase change temperature of TiO2, the heating rate is 3°C / min, the holding time is 2.5h, and cooled to room temperature by furnace cooling, air cooling or quenching in water, and then annealing is performed at 400°C and annealing time is 3h to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the size of the TiO2 nanoparticles is 20nm.
[0040] Step 3: Evaluation of the activity of TiO2 / ZnO piezoelectric catalyst Step 3.1: Weigh 100 mg of catalyst powder and add it to 100 mL of 10 mg / L Rhodamine B solution. After ultrasonic dispersion for 5 min, the suspension was placed in a dark environment and continuously magnetically stirred for 30 min to achieve adsorption-desorption equilibrium.
[0041] Step 3.2, transfer the solution obtained in step 3.2 to an ultrasonic generator, turn on ultrasonic and ultraviolet light, wherein the ultrasonic frequency is 30kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 35°C. Use a H2O2 quantitative detection kit to quantitatively detect the H2O2 production. Use an ultraviolet spectrophotometer (551nm) to test the piezoelectric photocatalytic H2O2 production efficiency of the sample, and calculate its piezoelectric photocatalytic efficiency.
[0042] Example 6 Step 1. Preparation of MoS2 nanosheets Step 1.1, 0.686g (NH4)6Mo7O 24 •4H2O and 1.269 g CH4N2S were dissolved in 100 mL deionized water and stirred to obtain MoS2 precursor solution.
[0043] Step 1.2, transfer the MoS2 precursor liquid to a 150 mL hydrothermal reactor, hydroheat in an oven at 220°C for 18 h, cool to room temperature, filter the resulting solid, wash it with distilled water several times, and then dry it in an oven at 60°C overnight to obtain a MoS2 nanosheet catalyst with a size of about 0.5 μm.
[0044] Step 2 Preparation of Fe, 2O3 / MoS2 piezoelectric catalyst Step 2.1. Under mechanical stirring, dissolve 10 mmol of oxalic acid in 50 mL of deionized water. At the same time, weigh 5 mmol of MoS and add it to the solution. Stir for 30 min, disperse it by ultrasound for 1 h, and heat it to 60 °C in a water bath. This is referred to as solution A.
[0045] Step 2.2: Weigh 10 mmol of FeSO4·7H2O and dissolve it in 50 mL of deionized water, referred to as solution B.
[0046] Step 2.3, add solution B dropwise into solution A, and react at 60°C for 20 min. After the reaction, filter by vacuum, wash with deionized water and ethanol three times, and dry in an oven at 60°C for 12 h.
[0047] Step 2.4: Heat-treat the Fe2O3 / MoS2 precursor obtained in step 2.2 at 500°C in a muffle furnace, with a heating rate of 2°C / min and a holding time of 3h. Then, take the Fe2O3 / MoS2 out of the muffle furnace and cool it to room temperature in air. Then, put the sample into the muffle furnace again and anneal it at 200°C for 4h to obtain a phase-transformation-enhanced Fe2O3 / MoS2 powder. The size of the Fe2O3 nanoparticles is 50nm.
[0048] Step 3: Evaluation of Fe2O3 / MoS2 piezoelectric catalyst activity Step 3.1. Weigh 100 mg of catalyst powder and 50 mg of Au nanoparticles and add them to a mixed solution of 5 mL of MeCN and 5 mL of NH4Cl (0.1 M). After ultrasonic dispersion for 5 min, the suspension was placed in a dark environment and continuously magnetically stirred for 30 min to achieve adsorption-desorption equilibrium.
[0049] Step 3.2, transfer the solution obtained in step 3.1 to an ultrasonic generator, turn on ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 40kHz, the ultraviolet lamp power is 3W, and the circulating water temperature is 45°C. The concentration of the precious metal in the solution during the dissolution process is measured by an inductively coupled plasma emission spectrometer to calculate the solubility, and calculate its piezoelectric photocatalytic efficiency.
[0050] Example 7 Step 1. Preparation of BiOCl nanoparticles Step 1.1. Weigh 2 mmol of bismuth nitrate, add it to 15 mL of ethylene glycol, and sonicate for 30 min to dissolve it. This solution is recorded as solution A.
[0051] Step 1.2, weigh 2 mmol of ammonium chloride and dissolve it in 60 ml of deionized water, which is called solution B. Add solution B dropwise into solution A, continue stirring for 1 hour, transfer the mixed solution to a 100 mL polytetrafluoroethylene reactor, keep it at 140°C for 12 hours, and cool it naturally to room temperature. Wash it with deionized water and ethanol three times each, and vacuum dry it at 60°C overnight to obtain BiOCl powder with a size of about 0.5 μm.
[0052] Step 2: Preparation of AgI / BiOCl piezoelectric catalyst Step 2.1. Add the required amount of silver nitrate into a beaker containing 40 mL of anhydrous ethanol and use ultrasonic treatment to fully dissolve it to obtain a silver nitrate solution.
[0053] Step 2.2, add 0.5 g of BiOC1 to the silver nitrate solution, ultrasonicate for 30 min to make it disperse evenly, recorded as solution C. Dissolve the required amount of KI in 40 mL of anhydrous ethanol, ultrasonicate for 10 min to dissolve it, recorded as solution D. Add solution D dropwise to solution C, and continue stirring for 2 h. Centrifuge the resulting sample, wash it with water and ethanol three times each, and dry it in vacuum at 60°C overnight.
[0054] Step 2.3, heat-treat the AgI / BiOCl piezoelectric catalyst obtained in step 2.2 at 150°C in a muffle furnace, with a heating rate of 5°C / min and a holding time of 5h. Then, take the AgI / BiOCl piezoelectric catalyst out of the muffle furnace and cool it to room temperature in air. Obtain a phase-change enhanced AgI / BiOCl piezoelectric catalyst. The size of the AgI piezoelectric catalyst nanoparticles is 100nm.
[0055] Step 3: Evaluation of the activity of AgI / BiOCl piezoelectric catalyst Step 3.1, weigh 100 mg of catalyst powder and 50 mg of lithium cobalt oxide powder and add them into 100 mL of citric acid aqueous solution. After ultrasonic dispersion for 5 min, the suspension is placed in a dark environment and continuously magnetically stirred for 30 min to achieve adsorption-desorption equilibrium.
[0056] Step 3.2, transfer the solution obtained in step 3.1 to an ultrasonic generator, turn on the ultrasonic wave and ultraviolet light, wherein the ultrasonic wave frequency is 50 kHz, the ultraviolet lamp power is 3 W, and the circulating water temperature is 70° C. The solubility is calculated by measuring the concentration of the metal in the solution during the dissolution process by an inductively coupled plasma emission spectrometer, and its piezoelectric photocatalytic efficiency is calculated.
[0057] Comparative Example 1 In this comparative example, the ZnO / TiO2 nanorod powder was heat treated at 700°C, and the rest was the same as in Example 1. The XRD spectra of the samples obtained in Comparative Example 1 and Example 1 are shown in the attached figure. Figure 2 As shown in the figure, when the heat treatment temperature rises to 800°C, the crystal form of TiO2 changes from anatase to rutile phase, and the (101) peak of wurtzite ZnO shifts to the right, which means that the crystal form transformation of TiO2 produces lattice distortion in ZnO crystal.
[0058] Comparative Example 2 It is basically the same as Example 1, except that after the heating treatment, the ZnO / TiO2 nanorod powder is subjected to water quenching cooling treatment, and the rest is the same as Example 1.
[0059] Comparative Example 3 It is basically the same as Example 1, except that after the heat treatment, the ZnO / TiO2 nanorod powder is annealed at 500°C for 2h, and the rest is the same as Example 1.
[0060] Comparative Example 4 The method is basically the same as Example 1, except that the ZnO / TiO2 nanorod powder is subjected to ultrasonic photocatalytic reaction at 35°C to degrade rhodamine B. The rest is the same as Example 1.
[0061] Comparative Example 5 The method is basically the same as Example 1, except that no ultrasonic wave is applied to the ZnO / TiO2 nanorod powder during the catalytic reaction to degrade Rhodamine B. The rest is the same as Example 1.
[0062] Comparative Example 6 It is basically the same as Example 1, except that ZnO is used for piezoelectric photocatalytic reaction, and the rest is the same as Example 1.
[0063] Effect verification: The rhodamine B of Example 1 and Comparative Examples 1-7 after reacting for 30 minutes was tested using an ultraviolet-visible spectrophotometer (UV-Vis). The results are shown in Table 1.
[0064] Table 1 Catalytic degradation efficiency of piezoelectric photocatalysts under different conditions
[0065] As can be seen from the table, after applying the piezoelectric field, the photocatalytic activity of TiO2 / ZnO increased by about 15%, which means that the dynamic piezoelectric field of ZnO can accelerate the photocatalytic degradation of dyes. The piezoelectric photocatalytic efficiency of TiO2 / ZnO after heat treatment at 800°C increased by about 250% and 38% compared with pure ZnO and TiO2 / ZnO heat treated at 700°C, respectively, which means that the ZnO lattice distortion caused by the phase transition of TiO2 can improve the piezoelectric photocatalytic activity of ZnO. Annealing the TiO2 / ZnO piezoelectric photocatalyst after heat treatment at 800°C or performing the piezoelectric photocatalytic reaction at a higher temperature (35°C) increased its piezoelectric photocatalytic efficiency by about 10% and 34%. This is because the lattice distortion caused by phase change is reduced by annealing or piezoelectric photocatalytic reaction at a higher temperature (35°C), which makes the lattice distortion in the best position, which can not only improve the piezoelectric field strength of ZnO but also facilitate the transfer of photogenerated carriers between TiO2 and ZnO, so that TiO2 / ZnO has excellent piezoelectric photocatalytic activity. The catalytic activity of TiO2 / ZnO piezoelectric photocatalyst quenched in water is reduced by about 23% compared with that of furnace cooling. This is because the excessive lattice distortion makes it difficult for photogenerated carriers to migrate between TiO2 and ZnO, thereby reducing its piezoelectric photocatalytic activity. In summary, it can be found that regulating the lattice distortion at the interface of TiO2 and ZnO through heat treatment process and keeping it in a suitable range can greatly improve the activity of TiO2 / ZnO piezoelectric photocatalyst.
Claims
1. A method for improving the activity of a zinc oxide piezoelectric photocatalyst, characterized in that: The specific steps are as follows: Step 1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, performing a hydrothermal reaction, centrifuging the precipitate, and then performing a heat treatment to obtain a single crystal ZnO nanoparticle powder; Step 2: Add the single crystal ZnO nanoparticle powder and butyl titanate to ethanol under ultrasound, add the mixture to a water-ethanol mixed solution for reaction, centrifuge, wash, dry, and then heat treat after the reaction, cool to room temperature and anneal under different processes to obtain phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, thereby improving the activity of zinc oxide piezoelectric photocatalyst.
2. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 1, characterized in that: In step 1, zinc oxide is replaced by inorganic piezoelectric catalysts and their modified, surface-modified or composite piezoelectric catalysts, etc., specifically including layered transition metal dichalcogenides, bismuth layered structure materials, wurtzite-based semiconductors, graphene, PVDF, g-CN or metal organic framework materials.
3. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 1, characterized in that: In step 2, TiO2 is replaced by other crystalline phase change materials, including other semiconductor oxides, metals and alloys, specifically titanium dioxide, zirconium oxide, vanadium dioxide, iron-based, titanium-based or aluminum-based.
4. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 1, characterized in that: The specific method of step 1 is: Step 1.1, dissolving zinc nitrate hexahydrate and hexamethylenetetramine in deionized water, wherein the dosage ratio of the zinc nitrate hexahydrate to the hexamethylenetetramine is 2:1, and the mass ratio of the zinc nitrate hexahydrate to the deionized water is 1:150, and stirring to obtain a hydrothermal solution; Step 1.2, transferring the hydrothermal solution to a reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100-110°C, the time is 6-8h, after the reaction is completed, the obtained precipitate is centrifuged, washed twice with deionized water and anhydrous ethanol respectively, and dried at 50-60°C for 12-16h to obtain a reaction powder; Step 1.3, placing the reaction powder in a muffle furnace for heat treatment, the heat treatment temperature is 800°C, the time is 2~4h, and after cooling in the furnace, single-crystalline ZnO nanoparticle powder is obtained. The morphology of the single-crystalline ZnO nanoparticles is rod-shaped, flake-shaped or spherical. The crystal form of the single-crystalline ZnO nanoparticle powder is a lead-zinc ore structure with piezoelectric properties, and the size of the nanoparticle powder is 100nm~10μm.
5. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 4, characterized in that: The specific method of step 2 is: Step 2.1, adding deionized water to the ethanol solution to obtain a water-ethanol mixed solution, wherein the volume ratio of deionized water to ethanol is 1:60-70; Step 2.2, the single crystal ZnO nanoparticle powder and butyl titanate are first added to ethanol and mixed under ultrasound, and then added to the water-ethanol mixed solution obtained in step 2.1, and stirred for 1 to 1.5 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a ZnO / TiO2 precursor; Step 2.3, placing the ZnO / TiO2 precursor in a muffle furnace for heat treatment, and cooling to room temperature, and then annealing to obtain a phase change enhanced ZnO / TiO2 piezoelectric catalyst powder, wherein the morphology of TiO2 in the ZnO / TiO2 piezoelectric catalyst powder is nanoparticles, the crystal form is anatase phase, and is uniformly coated on the ZnO surface, wherein the size of the TiO2 nanoparticles is 10~100nm.
6. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 5, characterized in that: In the step 2.2, the mass ratio of single crystal ZnO nanoparticle powder to butyl titanate is 10:3, the mass ratio of single crystal ZnO nanoparticle powder to ethanol is 1:15-20, and the mass ratio of single crystal ZnO nanoparticle powder to water-ethanol mixed solution is 1:15-20.
7. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 5, characterized in that: The heat treatment process temperature in step 2.3 is 600-800°C, the phase transition temperature of TiO2, the heating rate is 1-5°C / min, and the holding time is 0.5-3h.
8. The method for improving the activity of zinc oxide piezoelectric photocatalyst according to claim 5, characterized in that: The cooling method in step 2.3 includes furnace cooling, air cooling or quenching cooling in water; The annealing temperature is 300-500° C., and the annealing time is 1-5 hours.